Pengaruh Infrastruktur Jalan, IPM, Tenaga Kerja dan Upah Minimum terhadap Pertumbuhan Ekonomi dengan Investasi sebagai Variabel Moderasi di Indonesia Tahun 2018-2023 - Hukania, Helnanda; Ariyani, Diyah (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
This study aims to analyze the effect of road infrastructure, Human Development Index (HDI), labor, and minimum wage on economic growth with Investment as a moderating variable. This study uses secondary data in the form of panel data obtained from the official BPS website in Indonesia with an observation period of 2018-2023. The analysis method used is panel data regression and Moderated Regression Analysis (MRA) with E-Views 12 software. The results of the study show that the variables of road infrastructure, HDI, and labor have a significant positive effect, while minimum wages have a significant negative effect on economic growth. Investment is able to moderate the effect of road infrastructure, labor, and minimum wages on economic growth, but is unable to moderate HDI on economic growth. This study emphasizes the importance of realizing more effective and efficient investment so that it can support the role of road infrastructure, HDI, labor, and minimum wages in increasing the rate of economic growth in Indonesia.